Effect of Food-Simulating Liquids on the Leachability of Plasticizers from Dental Tissue Conditioners - Wan Ali, Wan Nor Syariza; Parker, Sandra; Patel, Mangala (European Journal of Dentistry, 2024)
Objective Tissue conditioners are composed of poly(ethyl methacrylate) (PEMA) powder and plasticizer/ethanol mix liquid. Butyl phthalyl butyl glycolate (BPBG) plasticizer is commonly used in tissue conditioners, but the main concern with phthalate plasticizer is its leachability and biocompatibility, especially the estrogenic activity and cytotoxicity of phthalate. Therefore, acetyl tributyl citrate (ATBC) plasticizer has been introduced and formulated as plasticizer in tissue conditioner; however its leachability characteristics are still unknown. Furthermore, the effect of foodsimulating liquids toward leachability of BPBG and ATBC plasticizers has not been documented. The objective of this study was to compare the effect of food-simulating liquids on the leachability of plasticizers and hardness of two experimental tissue conditioners containing BPBG and ATBC plasticizers.Materials and Methods Ten experimental materials were prepared using PEMA polymer powder with 95% plasticizer (BPBG and ATBC) and 5% ethanol by volume, using powder to liquid ratio of 1.67:1, and the thickness was controlled at 3 mm. Shore A hardness value was measured after immersion in distilled water, artificial saliva, 25% ethanol/water mix, 3% citric acid, and coconut oil at 37°C. Measurements were taken at 2 hours and 1, 2, 3, 4, 7, 10, 14, 21, 28, 42, 56, and 84 days. Six readings were taken for each sample and hardness change was calculated and statistically analyzed using Wilcoxon signed-rank test.Results Increase in hardness value was noted for both plasticizers over time with the highest increase was when immersed in coconut oil. Shore A hardness value was significantly higher in ATBC after 84 days of immersion in all food-simulating liquids. The increase in hardness is due to plasticizer/ethanol leaching; however, as ethanol content was the same (5%), the hardness change is attributed to the leaching of plasticizers.Conclusion Leaching of both plasticizers was highest in coconut oil indicating that tissue conditioners may have a shorter intraoral lifetime in patients eating high-fat diet.
Keywords: tissue conditioner; plasticizer leaching; food-simulating liquids; Shore A hardness